Methodologies of Designing Questionnaires Concerning the Dynamics and Structure of Specialists in an Economic Sector in an Economic Sector - Vasilica Ciuca; Liliana Grecu; Speranța Pârciog; Constantin Ciupagea; Radu Gheorghiu; Manuela Unguru (Revista de Economie Mondială, 2009)
On the labour demand side, in order to identify the match between skills and labour market demand, it is required a thorough analysis of structure and dynamic of specialists in an economic sector. The data necessary for this kind of analysis could not be found in the current statistical databases. Accordingly, it is necessary to carry out surveys for exploring the demand for skills.